Development and validation of LC-MSMS bioanalytical method for the analysis of Amlodipine and gliclazide in Human plasma - Alaama, Mohammed; Helal Uddin, A.B.M.; Mohamad, Huda Jamilah; Awang, Mohamed Saufi; Abbas, Syed Atif (2016)
Introduction: a simple, rapid and sensitive liquid chromatography-tandem mass spectrometric (LC–MS/ MS) assay method has been developed and fully validated for the simultaneous quantification of amlodipine and gliclazide in human plasma. Materials/method: Citerizine was used as internal standard (IS). In brief 100 ul of plasma spiked with amlodipine and gliclazide was taken in eppendrof tube and known amount of internal standard was added, then ACN was added and vortexed for 30 second. Samples were centrifuged and organic was collected and evaporated under nitrogen gas. All samples were reconstituted in mobile phase, filtered and injected into Waters BEH 2.1X50 mm, 1.7 micron C18 column. All samples were analysed using Waters Aquity UPLC-MSMS with Xevo TQD MS detector. Multiple reaction monitoring (MRM) mode was used for detection. The mobile phase consists of 0.1 % Formic acid and ACN with gradient elution program over 5 min. Results: The results of the intra-and inter-day precision and accuracy studies were well within the acceptable limits. All the analytes were found to be stable in according to conducted stability studies. Conclusion: The method is precise and sensitive enough for its intended purpose.